PENGARUH KOMUNIKASI KEPEMIMPINAN, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN TANAH DATAR - Yusrizal Yus; Yunia Wardi (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The working satisfaction has the important for the on-going life of an organization, including the government organization, for that purpose an organization needs to pay attention to the factors which influence the work satisfaction of the employees. The objective of this research is to know and to analyze the effects of the communication variables of a leader, the compensation and the work motivation on the Work Satisfaction of the employees at Dinas Perhubungan Komunikasi dan Informatika Kabupaten Tanah Datar. This research includes the quantitative approach. The population of the research is 74 participants by using Slovin Formula 43 samples are obtained. The techniques of sampling is Proportional Stratified Random Sampling. The data was managed by using path technique analysis by the help of SPSS software. The result of the research shows that the leader communication, the compensation and the work motivation has significantly influence the employees’ work satisfaction. The suggestion for this research is to the related stakeholders to give the contribution on the increasing the work satisfaction for the employees to increase the working performance. Key Word:       Leadership Communication, Compensation, Work Motivation and Work Satisfaction